Analisis efektifitas pemberian air kelapa muda dan madu terhadap penurunan tekanan darah pada pasien hipertensi - Winanda, Bayu; Chrisanto, Eka Yudha; Djamaludin, Djunizar; Novikasari, Linawati (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: The increase in hypertension in the Pasiran Jaya Community Health Center (Puskesmas) work area has seen an increase in hypertension patients, from 324 in 2021 to 421 in 2022. One non-pharmacological treatment is young coconut water and honey. Young coconut water is believed to lower blood pressure, while honey contains important compounds that can influence antioxidant activity. Purpose: To determine the effectiveness of young coconut water and honey on lowering blood pressure in hypertensive patients. Method: This quantitative study used a quasi-experimental design using a pretest-posttest approach with a control group design. This study was conducted in the Pasiran Jaya Community Health Center (Puskesmas) work area in Tulang Bawang in August 2023. The sample selection technique used purposive sampling. Results: Bivariate data analysis using a t-test on systolic and diastolic blood pressure testing yielded a p-value of 0.001 < 0.05 for systolic blood pressure and a p-value of 0.006 < 0.05 for diastolic blood pressure. Conclusion: The administration of young coconut water and honey is effective in reducing blood pressure in hypertensive patients. Keywords: Blood Pressure; Honey; Young Coconut Water. Pendahuluan: Peningkatan hipertensi di Wilayah Kerja Puskesmas Pasiran Jaya terdapat peningkatan penderita hipertensi dari tahun 2021 sebanyak 324 penderita dan pada tahun 2022 meningkat menjadi 421 penderita hipertensi. Salah satu pengobatan non-farmakologi yaitu air kelapa muda dan madu. Kandungan yang dimiliki air kelapa muda dipercaya dapat menurunkan tekanan darah. Sedangkan madu memiliki kandungan penting yang dapat mempengaruhi aktivitas antioksidan. Tujuan: Untuk mengetahui efektifitas pemberian air kelapa muda dan madu terhadap penurunan tekanan darah pada pasien hipertensi. Metode: Penelitian kuantitatif dengan rancangan Quasi Eksperimental menggunakan pendekatan pretest-posttest with control group design. Penelitian ini telah dilaksanakan di Wilayah Kerja Puskesmas Pasiran Jaya Tulang Bawang pada Bulan Agustus 2023 dengan teknik pemilihan sampel menggunakan sampling purposive sampling. Hasil: Analisa data bivariat Menggunakan uji T-Test pada pengujian tekanan darah sistole dan diastole didapat nilai p-value 0.001 < 0.05 pada tekanan darah sistole dan p-value 0.006 < 0.05 pada tekanan darah diastole. Simpulan: Terdapat efektifitas pemberian air kelapa muda dan madu terhadap penurunan tekanan darah pada pasien hipertensi. Kata Kunci: Air Kelapa Muda; Madu; Tekanan Darah.